Actuator Fault Decoupled Residual Generation on Lateral Moving Aircraft - Samiadji Herdjunanto; Adha Cahyadi; Bobby Rian Dewangga (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Implementation of time-scheduled maintenance is not suitable if it is applied for systems with many varieties of heavy workload and harsh environment since on that condition components degrade earlier that those under normal condition. Therefore it has been shifted to condition-based maintenance (CBM). One important aspect, among others, toward implementation of CBM method is fault isolation. The problem investigated in this paper is related todecouple residual generation for actuator fault isolation of an aircraft on lateral movement. The proposed solution for that problem is to implement combination of transformation matrix and special filter. Transformation matrix is used to convert feature locations of actuator faults to signature vectors. Moreover, the signature vectors will be processed further by special filter to generate decoupled residuals. It is assumed that the actuator is the only fault when the aircraft is on lateral movement. The result showed that special filter and transformation matrix can be designed so that the residual of aileron actuator fault is decoupled from the residual of rudder actuator fault.